Efficacy of ketoprofen for treatment of spontaneous, culture-negative, mild cases of clinical mastitis: A randomized, controlled superiority trial - Latosinski, G. S. [UNESP]; Amzalak, M. J. [UNESP]; Pantoja, J. C.F. [UNESP] (American Dairy Science Association, 2020)
The objective of this randomized, controlled superiority trial was to assess the efficacy of ketoprofen for the treatment of spontaneous, culture-negative clinical mastitis cases that were not treated with antimicrobials. Holstein cows from 3 herds were eligible for inclusion if they had mild or moderate culture-negative clinical mastitis cases in 1 quarter or more. Upon detection of clinical mastitis, farm personnel performed on-farm culture (OFC) using commercially available bi-plates. Samples used for OFC were also cultured in a research laboratory. Cows with culture-negative clinical mastitis that met the inclusion criteria were randomly allocated to 1 of 2 experimental groups: in the ketoprofen (KET) group, cows received an intramuscular injection of 3 mg/kg of ketoprofen upon confirmation of a negative OFC result; and in the control (CON) group, cows received no treatment or placebo. Milk samples were collected 14 and 21 d after detection of clinical mastitis for microbiological examination and somatic cell counting. Study outcomes were clinical cure (within 7 d after inclusion in the study), relapse (within 14 d after inclusion) and recurrence of clinical mastitis (15 to 90 d after inclusion), risk of new intramammary infection, and quarter milk somatic cell count at 14 and 21 d. We used Cox proportional hazards, logistic regression, and repeated-measures models to compare each outcome between groups. After exclusion of moderate cases (n = 6), a total of 123 clinical mastitis cases (CON = 58 and KET = 65) were used for analyses. Risks of clinical cure [83.08% (54/65) and 91.23% (52/57); hazard ratio = 1.20, 95% confidence interval (CI) = 0.82–1.76], relapse [19.23% (10/52) and 18.00% (9/50); hazard ratio = 1.09, 95% CI = 0.45–2.62], and recurrence of clinical mastitis [17.31% (9/52) and 18.00% (9/50); hazard ratio = 1.26, 95% CI = 0.49–3.38] were not different between the KET and CON groups, respectively. The odds of a new intramammary infection at 14 d [20.75% (11/53) and 29.79% (14/47); odds ratio = 1.76, 95% CI = 0.66–4.73] or 21 d [28.57% (12/42) and 15.22% (7/46); odds ratio = 0.45, 95% CI = 0.16–1.30] were not different between the KET and CON groups, respectively. Mean somatic cell count was not different between the groups at 14 or 21 d. The results of this study suggest that a single intramuscular injection of ketoprofen as sole treatment for OFC-negative, mild clinical mastitis did not reduce time to clinical cure, relapse or recurrence of clinical mastitis, risk of subsequent intramammary infection, or milk somatic cell count compared with untreated controls.
Keywords: bovine clinical mastitis; ketoprofen; therapy